The Contribution of Islamic Religious Education Teachers to the Empowerment of Out-of-School Youth through Islamic Values-Based Education - Ayatullah (Formad English Foundation NTB Jakarta, 2026)
This study is motivated by the limited synthesis of evidence concerning the contribution of Islamic Religious Education (IRE) teachers to the empowerment of out-of-school youth through Islamic values-based education, despite the growing need for inclusive educational approaches to address educational inequality and social exclusion. The study aims to systematically examine the educational roles of IRE teachers, analyze the implementation of Islamic values-based education, explore the contribution of community-based educational practices, and develop an integrated conceptual framework for youth empowerment. The research employed a qualitative Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Secondary data were collected from peer-reviewed journal articles published between 2021 and 2026 and retrieved from major academic databases, including Scopus, Web of Science, ScienceDirect, SpringerLink, Taylor & Francis Online, Wiley Online Library, Sage Journals, Emerald Insight, MDPI, ERIC, DOAJ, Crossref, and Google Scholar. The selected studies were analyzed using thematic analysis. The findings reveal that IRE teachers perform multidimensional roles as moral and spiritual educators, learning facilitators, and community educators who promote educational empowerment through the internalization of Islamic values, mentoring, role modelling, and community engagement. The review further identifies justice (adl), compassion (rahmah), responsibility (amanah), and moderation (wasatiyyah) as the core values underpinning educational empowerment. The study concludes that Islamic values-based education provides a holistic framework for strengthening educational access, character formation, social inclusion, and community resilience among out-of-school youth. Theoretically, this review advances Islamic education literature by proposing an integrated conceptual framework, while practically informing educators, policymakers, and community organizations in developing collaborative and inclusive educational programs. Future research should empirically validate the proposed framework across diverse educational and cultural contexts.